PEMBUKTIAN UNDANG-UNDANG BAGI PELAKU PELECEHAN SEKSUAL AKIBAT ULAH PENDERITA BIPOLAR - Firda Azzahwa; Hary Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Law enforcement regarding victims with disabilities has been widely found because people with disabilities are considered less responsive before the law, regarding perpetrators with disabilities it is rarely discussed because the quantity of persons with disabilities as a result of criminal acts is more inclined to victims, in this study the focus will be on perpetrators with disabilities who commit sexual violence because it does not allow persons with disabilities to commit crimes coupled with the reasons for this act due to a lack of understanding and education on matters related to reproduction, this was learned when they entered school, persons with disabilities certainly need special attention to deal with this so that they can distinguishing things that may or may not be done and the sanctions that are obtained when committing immoral acts, when persons with disabilities know that there are sanctions the possibility of violations will be avoided Darkan, this study aims to find out if perpetrators of mental disorders, especially bipolar sufferers, can be criminalized and find out the legal consequences for perpetrators of bipolar sufferers who commit sexual violence. This research uses normative research methods, namely the statutory and conceptual approach